(untitled) (Acta Polytechnica CTU Proceedings, 2023)
Developing Advanced Driver Assistance Systems (ADAS) and Autonomous Vehicles (AV) based on machine learning is generally an extensive and costly process. Due to the increasing complexity of autonomous systems, the need for extensive testing and validation arises. In recent years, computer simulation has been used for these purposes. Performing realistic simulations, especially for the purpose of computer vision-based systems, requires a high-quality, almost photorealistic virtual environment. This paper introduces U SMART ZONE, a high-fidelity virtual model of the Severní Terasa district in Ústí nad Labem, Czech Republic comprising of more than 7.5 km of drivable roads with a total area of approximately 1.4 km2 for human-in-the-loop and hardware-in-the-loop (HiL) simulations.